Mata Air Jolotundo: Studi Tentang Pandangan Masyarakat Muslim Terhadap Kekhasiatan Mata Air Jolotundo Desa Seloliman Mojokerto - Laila Wardatin; Masyhudi (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2020)
Abstract: The focus of this article examines the public's view of the Jolotundo spring. The problems discussed in this article are as follows: 1). How is the monograph of Seloliman village, Trawas district, Mojokerto district. 2). How is the existence of the Jolotundo spring 3). What is the public's view of the Jolotundo spring. Answers to the questions above the author answers using ethnographic methods. Researchers also use the theory of cognitive anthropology which was widely developed by Ward H. Goodenough. This study concludes that: 1). Seloliman Village has a predominantly Muslim population, in which there is a Jolotundo spring. 2). Jolotundo spring is a holy spring (amartha). From the existence of the Jolotundo spring which is spread among the people in general, namely as a medicine to cure diseases. 3). Nahdatul Ulama figures allow that if anyone believes that the Jolotundo spring is holy and can be used to cure all kinds of ailments, however, the spring must be believed to be an intermediary medium for healing diseases from Allah. Keywords: water springs, Muslim, medicine, fatwa